Bagaimana Pengaruh Paparan Iklan terhadap Brand Awareness serta Keinginan untuk Memainkan Game Mobile Legends pada Generasi Z di Kota Batam - Eryc Eryc; Elvin Whang (Journal on Education, 2023)
The research has the purpose to know how mobile legends advertising strategy from the brand awareness and intention to play. This research uses the quantitative method with a clausal approach. There are 3 variables involved in this research , which are Advertising Exposure (x1) and Brand Awareness (x2) as the independent variables, also Intention to Play (y) as the dependent variable. Researchers use questionnaires as means of collecting data in research with a total sample of 142 people.